SISTEM AKUNTANSI PEMBELIAN BAHAN BAKU SECARA KREDIT (Studi Pada PT. Hino Motors Manufacturing Indonesia) - Herlina Herlina; Asmawi Mangku Alam; Adzkia Putri Zhafirah Tanjung (POLITEKNIK LP3I JAKARTA, 2021)
In a trading company, the purchase of raw materials is the most important activity. The purpose of this writing is to find out more clearly about the accounting system for purchasing raw materials on credit that has been running at PT. Hino Motors Manufacturing Indonesia and to find out suggestions for improvement from the author so that the company's accounting system can run well. The data collection technique used was a literature study from 9 book sources, field studies by means of observation and interviews, and conducting research on PT. Hino Motors Manufacturing Indonesia. The accounting system for purchasing raw materials on credit that has been running at PT. Hino Motors Manufacturing Indonesia is good enough, but it is still not in accordance with Mulyadi's theory in his book